PENCIPTAAN FILM DOKUMENTER RUPA JIWA TOPENG SINGAPADU DENGAN GAYA EKSPOSITORI - Dewi, Ida Ayu Diah Indrani Camuni; Puriartha, I Kadek; Payuyasa, I Nyoman (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2025)
Rupa Jiwa Mask Singapadu is a documentary film exploring the beauty of mask art of Singapadu as one of Bali's cultural heritages rich in aesthetic value, philosophy, and spirituality. The film uses an exposure approach to describe the process of making masks, ranging from material selection to completion, and features in-depth interviews with local artists such as Cokorda Alit Artawan. This documentary also highlights the role of mask art in the traditional and spiritual traditions of Balinese people, while uncovering the challenges of preserving this art in the midst of modernization.